(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The phenomenon of the diffusion of social networks is not foreign to the artistic context: theorists,philosophers, and artists have long investigated its multiple aspects, highlighting the critical issues and interpreting the effects it has caused in the society in which we live. With the advent of Web 2.0 and the spread of a "participatory" Internet (consisting of blogs, wikis, and social networks), a new experimentation context for net art took shape. The new artistic proposals began to consider the Web as a primary element for social and political transformation. The purpose of this article is to present a series of artistic projects, conceived between 2000 and 2020, which are presented as social networks with artistic, activist, social, and community purposes. The nowadays essential connection to the social networks, due to the health situation derived from Covid-19, could have a more positive reading if we showcase the solidarity component that lies within them.